2016
DOI: 10.18052/www.scipress.com/ilcpa.64.69
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Decreasing Molecular Rigidity on Mesomorphism

Abstract: A Chalconyl homologous series: RO-C6H4-CH=CH-CO-C6H4-OC14H29(n) (meta) is synthesized and studied with a view to understand and establish the effect of molecular structure on Liquid crystal behaviour by reducing molecular rigidity through diminishing of a phenyl ring and a central carboxy or vinyl carboxy group from a molecule. Novel series consists of thirteen homologues (C1to C18). First member (C1) homologue is nonliquid crystal and the rest of the homologues (C2to C18) are enantiotropically ( C2to C5) nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Doshi et al reported chalconyl-ester linking group-based homologues series [25][26][27][28][29][30][31]. Previously, our research group also reported homologues series based on chalconyl-ester and chalconyl-vinyl ester central group with reference to two or three phenyl rings, respectively [32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Doshi et al reported chalconyl-ester linking group-based homologues series [25][26][27][28][29][30][31]. Previously, our research group also reported homologues series based on chalconyl-ester and chalconyl-vinyl ester central group with reference to two or three phenyl rings, respectively [32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 90%
“…The variations in the LC property and the degree of mesomorphism from homologue to homologue in the same series or from series to series for the same homologue are attributed to the changing magnitudes of molecular rigidity and flexibility due to changing molecular polarity and polarisability and other related parameters concerning the suitable magnitudes of intermolecular cohesions and closeness. The mesogenic properties of the presently investigated homologous series-1 are compared with structurally similar series-X [43] and -Y [49], as shown in Figure 6.…”
Section: Comparative Parametermentioning
confidence: 99%